Social myths and collective imaginaries - Bouchard, Gérard, 1943- (University of Toronto Press, 2017)
"Western or Eastern, ancient or modern, religious or scientific, myths are strikingly underestimated forces in contemporary society. In our rational, enlightened and supposedly civilized society myths have come to be perceived as the exclusive attribute of so-called pre-modern societies. In Social Myths and Collective Imaginaries, Gérard Bouchard conceptualizes myths as vessels of sacred values that transcend the division between primitive and modern. These vessels become so influential as to make an indelible impression on people's minds. We may no longer speak of Aphrodite or Gilgamesh but freedom, equality, social justice, environmentalism, democracy and nationalism are sacred values in our world. Nobody would deny that equality for all citizens in France, the right to property in the United States, or racial equality in South Africa are sacrosanct. Bouchard's refreshing and startling analysis reveals that as a sociological mechanism, myths have the power to bring societies together as well as tear themapart. In his own way, Bouchard awakens us to the transcendent power of myth that affects our daily lives, frequently unbeknownst to us."--